(untitled) (Gestão & Regionalidade, 2017)
The aim of this article is to understand the perception of public and private managers about the role of the municipal fiscal incentives policy in the local development of Montes Claros/MG. This work is a qualitative experience (accomplished through in-depth interviews) with 60 respondents of different institutions of the municipality of Montes Claros/MG on the thematic of municipal tax incentives, given the following research problem: in your perception, how does the municipal tax incentives policy contribute to the local development of the county? It was noted that municipal tax incentives in the analyzed case are less important than life conditions and the aesthetics of the municipality. It was possible to observe provocative fragilities in terms of systemic gains to the local economy when considering the externalities, since the companies are not part of a local development policy project that is able to potentiate the benefits of physical proximity between industries.